Spectropolarimetric follow-up of 8 rapidly rotating, X-ray bright FK Comae candidates. Issue 1 (26th May 2020) - Sikora, J; Rowe, J; Howell, S B; Mason, E; Wade, G A
ABSTRACT: Our understanding of the evolved, rapidly rotating, magnetically active, and apparently single FK Comae stars is significantly hindered by their extreme rarity: only two stars in addition to FK Com itself are currently considered to be members of this class. Recently, a sample of more than 20 candidate FK Comae type stars was identified within the context of the Kepler–Swift Active Galaxies and Stars (KSwAGS) survey. We present an analysis of high-resolution Stokes V observations obtained using ESPaDOnS@CFHT for 8 of these candidates. We found that none of these targets can be considered members of the FK Comae class based primarily on their inferred rotational velocities and on the detection of spectroscopic binary companions. However, 2 targets show evidence of magnetic activity and have anomalously high projected rotational velocities ( v sin i ) relative to typical values associated with stars of similar evolutionary states. EPIC 210426551 has a $v\sin {i}=209\, {\rm km\, s}^{-1}$, an estimated mass of $1.07\, M_\odot$, and, based in part on its derived metallicity of [M/H] = −0.4, it is either an evolved main sequence (MS) star or a pre-MS star. KIC 7732964 has a mass of $0.84\, M_\odot$, lies near the base of the red giant branch, and exhibits a $v\sin {i}=23\, {\rm km\, s}^{-1}$ . We find that these two objects have similar characteristics to FK Com (albeit less extreme) and that their rapid rotation may be inconsistent with that predicted for a single star evolutionary history. Additional observations are necessary in order to better constrain their evolutionary states and whether they have short-period binary companions.